Describing web services with semantic metadata. (24th January 2006) - Arroyo, Sinuhe; Lopez-Cobo, Jose Manuel
Web services are self-describing, self-contained applications that can be published, located, and invoked through common web protocols. Self-descriptions are in fact a form of metadata that provide details on the services offered. Semantic web services are, thus, an extension of such metadata-based descriptions to richer ontology-based description semantics. This paper provides an account on the main usage scenarios of semantic web services, as a roadmap for metadata research on the topic.